Pengembangan Formula Berbasis Bahan Pangan Lokal sebagai Alternatif PMT Balita Stunting (Kacang Merah dan Umbi Talas) - Angelina Agustin Ika Nur 'Aini; Fila Rachmad Ramadhan; Farida Nur Isnaeni (Yayasan Literasi Sains Indonesia, 2026)
The prevalence of malnutrition in Central Java in 2022 was 5.3%, which is considered serious. One effort to address malnutrition is the provision of calorie-dense supplementary foods based on local foods such as baked brownies. The purpose of this study was to develop a special diet formula based on red beans and taro tubers. This study was an experimental study with a completely randomized design (CRD) with three formulas (F375, F629, and F814). The results showed that the water content test of the baked brownie formula met the Indonesian National Standard (SNI) (<40%). The color test of each formula for indicator